(untitled) (Pulse, 2025)
Patent ductus arteriosus (PDA) is the commonest congenital heart disease. PDA can be closed by trans-catheter device implantation or surgical closure. Pediatric cardiologists have been closing the PDA with device with tremendous success. Although large PDA device closure followed by post device closure syndrome is rare, this clinical condition can be managed by pre device implantation evaluation of predictor factors. Our patient had large tubular PDA which was properly evaluated before ADO I device implantation and managed his post device closure syndrome evidenced by left ventricular dysfunction and sudden rise of systemic blood pressure. His post device closure syndrome and para device leak were properly managed during hospital stay and close follow up. Pulse Volume 16, Issue 2 2024, P: 35-38